Minimally invasive Ivor Lewis esophagectomy in the elderly patient: a multicenter retrospective matched-cohort study - Capovilla, Giovanni; Uzun, Eren; Scarton, Alessia; Moletta, Lucia; Hadzijusufovic, Edin; Provenzano, Luca; Salvador, Renato; Pierobon, Elisa Sefora; Zanchettin, Gianpietro; Tagkalos, Evangelos; Berlth, Felix; Lang, Hauke; et al. (Frontiers in Oncology, 2023)
Several studies reported the advantages of minimally invasive esophagectomy over the conventional open approach, particularly in terms of postoperative morbidity and mortality. The literature regarding the elderly population is however scarce and it is still not clear whether elderly patients may benefit from a minimally invasive approach as the general population. We sought to evaluate whether thoracoscopic/laparoscopic (MIE) or fully robotic (RAMIE) Ivor-Lewis esophagectomy significantly reduces postoperative morbidity in the elderly population. We analyzed data of patients who underwent open esophagectomy or MIE/RAMIE at Mainz University Hospital and at Padova University Hospital between 2016 and 2021. Elderly patients were defined as those > 75 years old. Clinical characteristics and the postoperative outcomes were compared between elderly patients who underwent open esophagectomy or MIE/RAMIE. A 1-to-1 matched comparison was also performed. Patients < 75 years old were evaluated as a control group. Among elderly patients MIE/RAMIE were associated with a lower overall morbidity (39.7% vs. 62.7%, p=0.005), less pulmonary complications (32.8 vs. 56.9%, p=0.003) and a shorter hospital stay (13 vs. 18 days, p=0.03). Comparable findings were obtained after matching. Similarly, among < 75 years-old patients, a reduced morbidity (31.2% vs. 43.5%, p=0.01) and less pulmonary complications (22% vs. 36%, p=0.001) were detected in the minimally invasive group. Therefore, minimally invasive esophagectomy improves the postoperative course of elderly patients reducing the overall incidence of postoperative complications, particularly of pulmonary complications.